The Effect of Using PORPE (Predict, Organize, Rehearse, Practice, Evaluate) Method on Students' Reading Comprehension in Descriptive Text of The Eleventh Grade of SMA Kejayaan Indonesia - Nudia Yultisa; Efrini Panjaitan; Conny Conny; Listra Eunike br Sbr (Departement of Mathematics Education, 2023)
This study aims to find: improving students' reading comprehension through the use of the PORPE strategy. This research uses a quasi-experimental design because it is comparable to collecting data of reading comprehension and provides a pre-test and a post-test to collect the data. The instrument used is a reading test. The sample of this research is class XI at KEJAYAAN INDONESIA SMA which consists of 16 students. Samples were taken using a sampling technique. Based on the findings, it was found that the students' scores in understanding the meaning of the reading text increased where the pre-test t-value (66.66) < t-table (83.33) It can be concluded that the increase in students' understanding of the meaning of a reading text increased significantly by using the PORPE strategy